Pain Management in Acute Pancreatitis: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Cai, Wenhao; Liu, Fei; Wen, Yongjian; Han, Chenxia; Prasad, Manya; Xia, Qing; Singh, Vikesh K.; Sutton, Robert; Huang, Wei (Frontiers in Medicine, 2021)
Background: Pain management is an important priority in the treatment of acute pancreatitis (AP). Current evidence and guideline recommendations are inconsistent on the most effective analgesic protocol. This systematic review and meta-analysis of randomised controlled trials (RCTs) aimed to compare the safety and efficacy of analgesics for pain relief in AP. Methods: A literature search was performed to identify all RCTs assessing analgesics in patients with AP. The primary outcome was the number of participants who needed rescue analgesia. Study quality was assessed using Jadad score. Pooled odds ratios (ORs) or weighted mean differences (WMDs) with 95% confidence intervals (CI) were analysed using a random-effects model. Results: Twelve studies comprising 699 patients with AP (83% mild AP) were analysed. The tested analgesics significantly decreased the need for rescue analgesia (3 studies, OR.36, 95% CI 0.21 to 0.60) vs. placebo or conventional treatment. The analgesics also improved the pain score [Visual Analogue Scale (Δ-VAS)] at 24 h (WMD 18.46, 0.84 to 36.07) and by the 3rd to 7th days (WMD 11.57, 0.87 to 22.28). Opioids vs. non-opioids were associated with a decrease in the need for rescue analgesia (6 studies, OR 0.25, 95% CI 0.07 to 0.86, p = 0.03) but without significance in pain score. In subgroup analyses, opioids were similar to non-steroidal anti-inflammatory drugs (NSAIDs) regarding the primary outcome (4 studies, OR 0.56, 95% CI 0.24 to 1.32, p = 0.18). There were no significant differences in other clinical outcomes and rate of adverse events. Other studies, comparing epidural anaesthesia vs. patient-controlled analgesia and opioid (buprenorphine) vs. opioid (pethidine) did not show significant difference in primary outcome. Study quality issues significantly contributed to overall study heterogeneity. Conclusions: NSAIDs and opioids are equally effective in decreasing the need for rescue analgesia in patients with mild AP. The relative paucity of trials and high-quality data in this setting is notable and the optimal analgesic strategy for patients with moderately severe and severe AP still requires to be determined.